ANALYSIS OF FACTORS RELATED TO PROFESSIONAL COMMITMENT OF PHARMACYSTS IN PHARMACY SERVICES - Abdul Rahman Kadir; Muhammad Sobarsyah; Cancerina, Aqua sylvii (Scientia integritas Utama, 2023)
This research aims to find a description about factors related to the professional commitment of pharmacists and it's attendance on pharmacy services for communities. This research was carried out in pharmacy services at Makassar city according to the types of pharmacy with a survey method using a questionnaire. The population were pharmacists and pharmacists assistance from three types of pharmacy services such as public service pharmacy, hospital pharmacy, and franchise or “BUMN” pharmacy. The sample was taken by proportionate stratified random sampling method from 279 pharmacists which was then found 72 samples proportionally. The data was then analyzed using multiple linear regression methods to find out the correlations between variables and then proceed to a t-test analysis to determine which variable is dominantly correlated to professional commitment of pharmacist in pharmacy services. The results show that motivation, competence, leadership, and attitude do simultaneously and significantly correlate to the professional commitment of pharmacists in pharmacy services. But in part, only motivation and competence were significantly correlated to the professional commitment of the pharmacist which was more dominant in motivation.